Proteomic analysis of microglia during LPS‐induced acute neuroinflammation: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Cartier, Anna; Yeung, Bertrand; Moyron‐Quiroz, Juan; Gao, Qing; Hunag, Tse Shun; Nazor, Kristopher; Tan, Miguel
Abstract: Background: Dysregulation of microglia function is associated with neuroinflammation. A major limitation in understanding microglial contribution to cellular processes and their role in disease has been the lack of tools to specifically distinguish these cells from other myeloid cells. Method: We generated and validated a rat monoclonal antibody against a highly selective microglia marker P2RY12. We utilized LPS administration as a model for neuroinflammation to assess alterations in P2RY12 expression, a homeostatic protein. To gain better understanding of microglial function, we assessed their proteomic profile using BioLegend's proprietary technology, TotalSeq™, which allows simultaneous analysis of both the transcriptome and proteome at the single‐cell level. Result: Mice were injected with either PBS, low or high dosages of LPS daily for 4 days after which microglia were harvested from the brain. Isolated cells were co‐stained with CD11b, CX3CR1, and P2RY12 as general markers for microglia. Flow cytometric quantification using live cells showed a significant increase in CD11b + expression in both low and high dose LPS treated mice compared to the control untreated group. Low and high dose LPS injections led to a significant reduction in P2RY12 and CX3CR1 expression in these cells. These data are consistent with a decrease in P2RY12 expression under inflammatory conditions. We utilized a panel of 200 antibody‐oligonucleotide conjugates from our TotalSeq™ platform, including P2RY12, CD11b, CD45, and CX3CR1, to analyze differentially expressed proteins under normal and LPS‐induced inflammation in mice. Conclusion: These studies help elucidate the diversity and physiology of microglia, and potentially aid in the discovery of novel markers in response to neuroinflammation. Our future goal is to extend our studies and use our platform to assess alternations in microglial response in neurodegeneration.